Conversation with Eileen Julien - Adesokan, Akin; Panaite, Oana (Research in African literatures, 2025)
This conversation took place on January 16, 2023, a date that marked that year’s celebration of the Martin Luther King Jr. Day, in Eileen Julien’s Bloomington home. Intended as a series of reflections, inspired by her decades-long involvement with African studies on the topics already explored in the 2020 symposium “Pluralism and the Engaged Humanities” such as overcoming institutional blockages, bridging disciplinary gaps, elaborating new methodologies, forging collaborative projects that bring together the local and the global, and the long-term social impact of academic communities, the dialogue offers insights into Julien’s own trajectory as it intersects with major figures and resonates with milestone moments that have shaped the field of African literatures and beyond.